Analisis Biaya Produksi Pencetakan Buku LKS di CV Pustaka Cendekia Menggunakan Metode Full Costing - Ahmad Zaenal Hakim; Abu Darim (STIKes Ibnu Sina Ajibarang, 2023)
The aim of this study is to analyze the calculation of production costs for worksheets at CV Pustaka Cendekia using the full costing method. This type of quantitative research. This study uses primary data and secondary data. Data collection techniques using interviews and documentation.The results of the research. Calculation of the cost of production using the full costing method at CV Pustaka Cendekia is to calculate all costs incurred in the production process of LKS books. From the results of the analysis, the total costs incurred to produce 1 LKS book is Rp. 2044. By using this calculation, for 1 LKS book, the company will get a profit of Rp. 1,456 (selling price Rp. 3,500– Rp. 2,044).